Enhancement of Thermochemical Energy Storage by Alkali Metal Chloride Salts-Doped Ca-Based Sorbents: A Combined DFT and Experimental Study - Dehao Kong; Nan He; Qicheng Chen; Binjian Nie; Yingjin Zhang; Nan An; Liang Yao; Zhihui Wang (Molecules)
In this paper, the enhancement of thermochemical energy storage by alkali metal chloride salts-doped Ca-based sorbents is revealed by experiments and DFT calculations. The results indicate that NaCl and KCl doping increases the reaction rate and cycle stability. Compared to CaO, the conversion of NaCl-CaO and KCl-CaO after one cycle is increased by 59.1% and 61.9%, respectively. This enhancement originates from the oxygen vacancies generated by Na2O and K2O and the significantly increased surface area by CaCl2 as well as the sintering delay. The synergistic effect between Na2O, K2O, and CaCl2 increases the reaction rate of calcium-based materials. Meanwhile, the penetration of low-viscosity molten NaCl and KCl into the calcium-based materials successfully segregates the CaO grains and allows the calcium-based material to maintain the porous structure after 80 cycles, thus exhibiting a high effective conversion rate. In addition, the KCl-CaO composites show the best combined performance in terms of effective conversion and averaged thermal energy density. This work paves the way for the application of chloride salts-doped calcium-based materials.